2022
DOI: 10.3390/jrfm15110511
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Financing in Africa during the COVID-19 Pandemic

Abstract: Access to finance by small-to-medium-enterprises (SMEs) remains an enigma that still warrants further research. The COVID-19 pandemic has exacerbated the funding gap and necessitated the need for entrepreneurs to seek alternative financing due to tight credit rationing by the traditional finance institutions. There is a marked increase in demand for alternative online finance known as crowdfunding amid social distancing and lockdowns occasioned by the COVID-19 pandemic. The main objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Similarly, Mamaro and Sibindi (2022) found that SMEs' access to Finance is positively associated with their growth and innovation. Mujeri et al (2020) note that SMEs have limited options in obtaining funding, with many SMEs being obliged to receive bank financing under tight conditions that are not beneficial to their enterprises' repayment capability.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, Mamaro and Sibindi (2022) found that SMEs' access to Finance is positively associated with their growth and innovation. Mujeri et al (2020) note that SMEs have limited options in obtaining funding, with many SMEs being obliged to receive bank financing under tight conditions that are not beneficial to their enterprises' repayment capability.…”
Section: Introductionmentioning
confidence: 93%
“…Repayment plans are also critical to SMEs' financial resilience. Flexible repayment plans can help SMEs manage their debt burden during economic uncertainty, enabling them to remain financially stable and avoid defaulting on their loans (Mamaro & Sibindi, 2022;Msomi & Olarewaju, 2022). However, many SMEs in South Africa need more flexible repayment plans, which can lead to default and bankruptcy (Fatoki, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that as a result of the pandemic, the need to obtain additional funding for businesses and the demand for alternative financing-in particular through crowdfunding platforms-have increased significantly. However, the COVID-19 pandemic also caused a decrease in participation in crowdfunding and reduced its effectiveness for businesses [50].…”
Section: Covid-19 Impacts On the Business Sectormentioning
confidence: 99%
“…The sustainability of entrepreneurs is considered to be a major engine of economic growth and development, mainly because it creates jobs and innovation (Mamaro and Sibindi 2022). This has directed African governments to encourage the establishment of small and medium-sized enterprises across the continent.…”
Section: Introductionmentioning
confidence: 99%